Career Guidance Model in Independence of Deaf Children in Time After Special Senior High School - mega iswari (Department of Special Education, 2017)
Career guidance model for deaf children in time after Special Senior High School consists of various skills that can be done as the provision in order to be independent in the future life. The problem of this study is learning skills for students who experience barriers hearing at Special Senior High School. The purpose of this study is to test whether there is influence of career guidance model for deaf children in facing the workforce so that they can be independent in the future life. The research method that is used in this study is Research Development (R & D) expressed by (Borg & Gall, 2003). The method of research is done using steps developed by (Borg & Gall, 2003). The Research is conducted in Payakumbuh city for certain skills such as culinary, fashion, aesthetic and other skills adjusted by potential area. The training is conducted for children who follow the subjects of expertise based on the Model of the Career Guidance that has been designed and developed as appropriate regional potential. In order to test the effectiveness of career guidance for self-relying children, it uses statistical techniques U Test by Mann Whytney. The results showed that the Career Guidance Model that is implemented for self-relying deaf children proven to be effective in improving the ability in conducting various types of skills that is given in accordance with their ability in time after Special Senior High School. It is proven from the result of U Test by Mann Whytney that is Uhit > Utab. This means that the guidance career model is effectively performed by deaf children, so they have skills in conducting various types of work that suits their ability so that they have the independence for the future life.